2023
DOI: 10.1002/pits.23084
|View full text |Cite
|
Sign up to set email alerts
|

“At Some Point We're Going to Reach Our Limit”: Understanding COVID‐19's impact on teacher burnout and subjective mental health

David T. Marshall,
Natalie E. Smith,
Savanna M. Love
et al.

Abstract: Teachers have faced a variety of challenges since the onset of COVID‐19 in the spring of 2020, including increased workloads, a range of modalities, and COVID‐19 protocols. The challenges associated with teaching during the COVID‐19 pandemic have led to increased burnout and stress, as well as diminished well‐being and mental health in teachers. This study seeks to explore teacher burnout and subjective mental health from the start of the pandemic to the end of the 2020–21 school year. To better understand tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
2
3
0
Order By: Relevance
“…The current study's findings align with previous work on teacher well-being and the role of administrative support [12][13][14]. Specifically, the low teacher morale is unsurprising as Marshall et al [15] found teachers had lower morale at the end of the 2020-2021 school year. What is concerning is that the current findings suggest the low morale has continued through another school year.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The current study's findings align with previous work on teacher well-being and the role of administrative support [12][13][14]. Specifically, the low teacher morale is unsurprising as Marshall et al [15] found teachers had lower morale at the end of the 2020-2021 school year. What is concerning is that the current findings suggest the low morale has continued through another school year.…”
Section: Discussionsupporting
confidence: 85%
“…Several factors were considered when developing the survey used to answer this study's research questions. Research we had conducted during the pandemic prior to this study suggested that teachers' workloads, stress levels, and burnout were elevated during the crisis [6,11,15]. Additional studies echoed similar findings [7,13,25,54,55].…”
Section: Survey Developmentsupporting
confidence: 62%
See 3 more Smart Citations